2016
DOI: 10.1007/s00223-016-0212-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Physical Exercise on Markers of Cellular Immunosenescence: A Systematic Review

Abstract: Aging affects negatively the immune system, defined as immunosenescence, which increases the susceptibility of elderly persons to infection, autoimmune disease, and cancer. There are strong indications that physical exercise in elderly persons may prevent the age-related decline in immune response without significant side effects. Consequently, exercise is being considered as a safe mode of intervention to reduce immunosenescence. The aim of this review was to appraise the existing evidence regarding the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(34 citation statements)
references
References 107 publications
2
31
0
1
Order By: Relevance
“…While studies in different experimental setups suggested that ET may improve the ability of the immune system to respond to deleterious stimuli, others demonstrated that intense ET may cause transient immune suppression . Several lines of evidence in our study demonstrate that ET modulates PLP‐autoimmunity rather than inducing general immune suppression.…”
Section: Discussionsupporting
confidence: 46%
“…While studies in different experimental setups suggested that ET may improve the ability of the immune system to respond to deleterious stimuli, others demonstrated that intense ET may cause transient immune suppression . Several lines of evidence in our study demonstrate that ET modulates PLP‐autoimmunity rather than inducing general immune suppression.…”
Section: Discussionsupporting
confidence: 46%
“…13, 35, 36 Increasing leukocytes and NK cell counts have been reported in the blood of athletes during exercise, 37, 38 while a decrease in the numbers of peripheral immune cells – predominately CD4 T cells and NK cells – has been observed during the recovery phase of exercise. 39 Overall, our observations in exercising versus sedentary mice are well in line with these rodent and human data.…”
Section: Discussionmentioning
confidence: 99%
“…The available scholarly literature seems to suggest that chronic exercise is a safe mode of intervention to prevent immunosenescence, chronic low-grade inflammation and improve the effectiveness of flu vaccination in elderly populations without harmful side effects ( 22 24 ).…”
Section: Physical Activity As a Tool To Counteract Immunosenescencementioning
confidence: 99%
“…Acute exercise impacts on circulation and leaves blood to travel to tissues where they are more likely to encounter infected cells or body cells that have become cancerous. Some studies seem to suggest that the acute effects of exercise (e.g., apoptosis of some cells) can stimulate a mobilization of hematopoietic stem cells from bone marrow and of senescent immune cells from the peripheral tissues to the circulation ( 22 , 52 – 55 ). This could justify and explain why in older subjects, in which these mechanisms are impaired by aging, response to acute exercise is different from younger individuals, as shown by some studies reported in Table 2 .…”
Section: Impact Of Acute Exercise On Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation